Solving problem of semantic terminology in digital library - Herlina Jayadianti (Universitas Ahmad Dahlan, 2017)
Effective information access involves the semantic interaction between users in searching activity to diverse information in the Digital Library. This is the focus of this research. The weakness of the online library system that is running is the difficulty of users looking for data collection library. There are many different perceptions that have the same meaning (synonym) in in terms of library collections such as Author and Writer. Therefore, in this research will focus on mapping between terminologies that supports to detect different meaning of perceptions .This technique can be considered as an attempt to understand the difference between perceptions in the interaction between users and information in digital libraries.